Numerical modeling of deformation in carbonates and implications for the formation of karst - Juliana Gomes Rabelo; Aline Theophilo Silva; Francisco Hilário Rego Bezerra; Anderson Moraes (Geologia USP. Série Científica, 2015)
The effect of the presence of fractures on fluid flow in reservoir is nowadays a fundamental theme of interest to the oil industry. In the case of carbonate rocks, the study of the contribution of fractures on reservoir efficiency becomes more complex due to the reactive nature of these rocks to circulating fluid and the high tendency to form karst. The fractures act as agents that focus fluid percolation and exert structural control on the formation of karst. For the oil industry, this scenario can be favorable became of the increasing of porosity and permeability of secondary fractures, but also poses risks to the operation. This article investigates, under the geomechanical point of view, how the presence of fractures influence the development of karst observed in carbonate rocks. The Jandaíra Formation was selected as an analogue geomaterial to fractured carbonate reservoirs in marginal basins of Brazil. The methodology adopted for this study included: (i) the use of satellite images, an UAV; (ii) Numeral modeling of the effect of the current tensions on the flagstone structures. Comparing the results of numerical modeling to the mapping performed on the images, it was found that the regions of the numerical models where the highest values of dilatancy occur coincided with local areas in the field (fault terminations and cross fractures), which represent the concentration of dissolution and karst formation. This work has established that there is a possible relationship between the stress concentration and the dissolution along the structural fabric observed in fractured field flagstones and showed that the dilatancy process is probably responsible for the occurrence of preferential dissolution by fractures in carbonate rocks.